Pengaruh Konsumsi Metformin terhadap Kejadian Anemia pada Penderita Diabetes Melitus Tipe 2 - Nugroho, Fajar Prianto; Wisnuwardhani, Ratih Wirapuspita (Indonesian Journal of Medical and Pharmaceutical Science, 2025)
Background: Diabetes mellitus is a chronic situation which is indicated by blood sugar levels that is higher than normal values, encompassing two types: type 1 and type 2. Type  2, also known as non-insulin dependent type of diabetes mellitus, can be treated managed with oral  anti-diabetic drugs (OADs). Metformin is a routinely used medication for type 2 diabetes and  is associated with long-term vitamin B12 deficiency,potentially leading to anemia. This study aimed to study the impact on metformin usage on the occurrence of anemia in type 2 diabetes mellitus patients at the Clinic in region S. Methods: This research employed a quantitative observational analytical approach with a cross-sectional data collection. The sample consisted of 62 individuals with type 2 diabetes mellitus who were taking metformin and were registered in the PROLANIS program at the Clinic in region S. Venous blood samples were collected and analyzed in the laboratory.The Pearson test was used to analysed the data. Results: The findings of this study indicated that the distribution of blood hemoglobin levels within the normal range, with an average hemoglobin level of 12.6 grams/dL. The usage of metformin did not have an effect on blood hemoglobin levels. Conclusion: This study concluded that metformin usage does not impact hemoglobin levels in patiens with type 2 diabetes mellitus.